2005
DOI: 10.1242/jcs.01553
|View full text |Cite
|
Sign up to set email alerts
|

Expression of connexins during differentiation and regeneration of skeletal muscle: functional relevance of connexin43

Abstract: The molecular mechanisms regulating skeletal muscle regeneration and differentiation are not well understood. We analyzed the expression of connexins (Cxs) 40, 43 and 45 in normal and regenerating tibialis anterior muscle and in primary cultures of differentiating myoblasts in adult and newborn mice, respectively. Cxs 45 and 43, but not 40, were strongly expressed in normal muscle and their expression was upregulated during regeneration. Furthermore, the functional role of Cx43 during differentiation and regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 79 publications
(83 reference statements)
12
101
1
Order By: Relevance
“…Cx43 protein is the predominant connexin in skeletal muscle and its involvement in myogenesis and muscle regeneration have been well documented [6,[23][24][25]. We have demonstrated that expression levels of Cx43 are greatly enhanced by S1P in C2C12 skeletal myoblasts and provided the basis for considering the gap junctional protein as an intracellular target of the pro-myogenic action of the sphingolipid [6].…”
Section: Introductionmentioning
confidence: 63%
“…Cx43 protein is the predominant connexin in skeletal muscle and its involvement in myogenesis and muscle regeneration have been well documented [6,[23][24][25]. We have demonstrated that expression levels of Cx43 are greatly enhanced by S1P in C2C12 skeletal myoblasts and provided the basis for considering the gap junctional protein as an intracellular target of the pro-myogenic action of the sphingolipid [6].…”
Section: Introductionmentioning
confidence: 63%
“…Our in vivo and in vitro results indicate that KCs express at least Cx43 but they might also express other Cx types as other macrophagic cells do. For example, monocyte/ macrophages also express Cx37 (21) and Cx45 (19) and microglia also express Cx36 (22).…”
Section: Discussionmentioning
confidence: 99%
“…To rule out the possibility that microinjected LY might be released to the extracellular space and then incorporated to neighboring cells via organic anion transporters or pannexin1 hemichannels activated by a rise in intracellular free Ca 2+ concentration through P2X channels (17), dye coupling assays were performed either in the presence of probenecid (18), an organic anion transporter blocker, or oxidized ATP, a P2X channel blocker (19). The dye transfer of LY to neighboring cells after microinjection of LY into a single cell was not altered by the presence of 50 μM probenecid or 100 μM oxidized ATP (for each compound, n = 4, Fig.…”
Section: Treatment With Lps Plus Ifn-γ Induces Intercellular Communicmentioning
confidence: 99%
“…Such morphogenetic control could be exerted by GJC-mediated changes in differentiation (Zhang et al, 2002;Araya et al, 2003Araya et al, , 2005Gu et al, 2003;Hirschi et al, 2003), proliferation (Paraguassu-Braga et al, 2003;Pearson et al, 2005), or cell migration (Minkoff et al, 1997;Huang et al, 1998;Lecanda et al, 2000;OviedoOrta et al, 2002;Kjaer et al, 2004). To integrate GJC-dependent signals into the systems that control complex morphology, it is necessary to understand the factors regulating spatial flows of signals through gap junctions.…”
Section: Behavior Is Dependent Upon Gap Junction (Gj) -Mediated Signalsmentioning
confidence: 99%